HUBUNGAN PEMAHAMAN MATERI TENTANG LAYANAN ORIENTASI DENGAN PENYESUAIAN DIRI SISWA KELAS VII SMPN 18 - Anibah, Anibah; Astuti, Indri; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe main objective of this research is to obtain objective information and to describe the relationship of material understanding about orientation service with students' adjustment in Junior High School 18 Pontianak. The method used is descriptive method with quantitative approach by means of statistics and described descriptively. The sample in this research is 51 students of class VII SMPN 18 Pontianak. Data collection techniques are indirect communication techniques. The data collection tool is a questionnaire. Data analysis techniques using descriptive analysis techniques and product moment correlation analysis. Based on the results of data analysis shows that the understanding of the material about service orientation of students of class VII SMPN 18 Pontianak reached 75.67%, the achievement is in the good range. Meanwhile, Adjustment of students of class VII N 18. pontianak reaches 82.33% which is in very good range. The result of product moment correlation of both variables is obtained rhitung = 0,298 which means show that there is positive correlation between material understanding about orientation service with self adjustment of class VII student of SMPN 18 Pontianak. If the material understanding about the orientation service is better, then the better the adaptation of the students of class VII SMPN 18 Pontianak. Vice versa. Keywords: Material understanding, Orientation service, Adjustment